Some places more than others - e uthor (New York : Bloomsbury Children's Books, 2019)
Amara visits her father's family in Harlem for her twelfth birthday, hoping to better understand her family and herself, but New York City is not what she expected.
School Library Journal starred, August 2019
Booklist, July 2019
Kirkus Review, June 2019
4.6
5-8
750L
Keywords: Family life -- New York (State) -- Harlem -- Juvenile fiction; African Americans -- New York (State) -- New York -- Juvenile fiction; Harlem (New York, N.Y.) -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Family life -- New York (State) -- Harlem -- Fiction; African Americans -- New York (State) -- New York -- Fiction; Harlem (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction